Effect of Work Motivation and Reward on Job Satisfaction Online Gojek Driver in Banjarmasin, Indonesia - Erviani, Dini; Husnurrofiq, Husnurrofiq; Purboyo, Purboyo (PT. Riset Press International, 2023)
This study aims to examine the effect of work motivation and reward variables on job satisfaction variables for Gojek online drivers in the city of Banjarmasin, Indonesia. The design of this research is research with quantitative methods and is afield survey research by taking primary data sources. The research population is Gojek Online drivers in the city of Banjarmasin and a sample of 30 respondents using a purposive sampling method. The data was processed by analyzing multiple linear regression data with the help of the SPSS test tool. The statistical test results and the results of the hypothesis in this study conclude that the work motivation variable and the reward variable simultaneously have a positive and significant effect on the online Gojek driver job satisfaction variable in Banjarmasin City, while the partial test results for the work motivation variable do not have a significant effect on the job satisfaction variable. Online Gojek drivers in Banjarmasin City, and the reward variable partially has a positive and significant effect on the J variable ob Satisfaction Gojek Online Drivers in Banjarmasin City, this research only takes objects in Banjarmasin city, it is hoped that further research can expand objects in other cities in Indonesia.